Choosing two technologies that best suite for making voter ID card - Aftab, Afzal; Abdullah, Md. Tareq (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2008.